Prospecção geofísica para delimitação do contato das formações Itapecuru e Codó no município de Jacundá-PA - MENDES, Marcelo Fernandes (2019)
The city of Jacundá, east of Pará State, has an incipient public water supply system, from few flow seasoned superficial source, that provides less than 20% of the population. Tubular shallow and open wells are the most used sources for private, limited and seasonal use. The flow from two deep tubular wells, drilled in Jacundá City, indicates this source as a good alternative for the solution for the local water supply. The city of Jacundá is seated on the edge of Parnaíba Sedimentary Basin. On the local, the coverage is constituted of non consolidated sediments and rocks of Itapecuru Formation, superimposed on the rocks of Codó Formation. Although having good aquifers, the Itapecuru Formation that constitute the coverage in Jacundá city it has little thickness and them its hydric potential is weak and seasonal. The Codó Formation, has restrict permeability and a thick packet of shale, but a good intercalation of sandstone. It means that this formation can be supply aquifer for the local. Wells drilled in the city that reach the sandstone intercalation had a flow in the meaning of 10m3/h. This fact gave reason for this geophysical study, determinating the top of Codó Formation, aiming to contribute for the planning and management of the public water supply in the city. It was utilized six Vertical Electric Sounding and one Well Log. The six VES had a preliminary interpretation. And, the detailing of the offered strata by the Well Log served to clarify the VES number 6, adjacent to the drilled well. The obtained model of VES number 6 was introduced in the interpretation of the other five VES, generating more representative models of the subsurface of the local. As a result, this study offer the mapping of the contact between Itapecuru and Codó Formations on the city of Jacundá, pointing the superior edge of the zone with good hydric potential which can mean the solution for the water supply management in the city of Jacundá.